New estimates of the costs of adverse events in patients with cancer - Achal Patel; Robert Schuldt; Jesse Sussell (PLoS ONE, 2025)
The cost of adverse events (AEs) is a critical component of healthcare economic models for cancer treatment; however, few comprehensive estimates of these costs exist. Previous studies focused on costs related to specific AEs, cancer types, or treatment regimens. This study assesses the incremental costs of AEs across 13 cancer types by applying the most current diagnosis schema (International Statistical Classification of Diseases and Related Health Problems [ICD-10]) to patients diagnosed between 2016 and 2022. Data were acquired from US insurance claims and included adult patients who were diagnosed and treated for breast, pancreatic, bladder, lung, prostate, colorectal, skin, liver, head and neck, non-Hodgkin lymphoma, follicular lymphoma, multiple myeloma, or chronic lymphocytic leukemia cancer. We selected 54 AEs for analysis based on their frequency of occurrence, relevance based on severity, and availability of ICD-10 diagnostic codes. We matched patient treatment episodes (the period from initiation of a distinct treatment regimen until discontinuation, change of treatment, or end of data availability) for patients experiencing a specific AE to treatment episodes of similar patients not experiencing that same AE in a 1:1 ratio. We generated estimates for AEs of any severity, severe AEs, and individual tumor types. Our analyses evaluate 392,566 treatment episodes from 110,791 patients. In pooled analyses across tumor types, incremental costs for AEs of any severity (with ≥ 100 treatment episodes) ranged from - $488 for photosensitivity to $29,331 for allergic reaction. Incremental costs for severe AEs (with ≥ 50 treatment episodes) ranged from $16 for dizziness to $18,841 for gastrointestinal bleeding. This study provides a comprehensive assessment of the economic burden of AEs in cancer care and generates a range of estimates to be used as inputs in future economic models.